The extracellular domain of SaNSrFP binds bacitracin and allows the identification of new members of the BceAB transporter family - Mammen, Christian; Gottstein, Julia; Cea, Pablo; Tantsur, Kira; Reiners, Jens; Bonus, Michele; Gohlke, Holger; Smits, Sander H. J. (Frontiers in Microbiology, 2025)
Peptidoglycan serves as the first permeability barrier of Gram-positive bacteria. Intermediates of the peptidoglycan synthesis cycle are typical targets of antimicrobial compounds, including the peptide antibiotics nisin and bacitracin. In human pathogenic bacteria, gene clusters have been identified that are upregulated to confer resistance against these compounds. One such cluster found in Streptococcus agalactiae encodes a Bacitracin efflux (BceAB)-type ATP binding cassette transporter, SaNsrFP, and an associated two-component system, SaNsrRK. SaNsrFP has been shown to confer resistance against multiple antimicrobial peptides in vivo, with highest activity against bacitracin. Like other BceAB-type ABC-transporters, SaNsrFP features a large extracellular domain (ECD) that determines the substrate spectrum. Here, we report the purification and in vitro characterization of the SaNsrFP complex. Measuring the ATPase activity in the presence and absence of bacitracin showed that the binding of bacitracin allosterically modulates ATPase activity. By expressing and purifying only the soluble ECD of SaNsrP, we could show through two in vitro binding assays that this segment alone is responsible for bacitracin binding and then explored the putative binding mechanism using molecular docking. Additionally, we assessed the structural conservation of the ECD across 24 BceAB-type ABC-transporters with the AlphaFold database. Enabling us to create a first classification within this superfamily based on the structural fold of the ECD.